RELIGIOUS BELIEFS AND PRACTICES OF THE HILL KHARIAS OF MAYURBHANJ IN ODISHA, EAST INDIA - FAGUTUDU,; MOHAPATRA, RATNAKAR (International Journal of Psychosocial Rehabilitation, 2020)
This article is intended to analyze religious Beliefs and Practices of the Hill Kharia Tribe of Mayurbhanj district inOdisha, India. It had unique rituals characteristics, which is overlooked by most of the current community society. In order to investigate the primal religion of Hill Kharia Tribe in Odisha state, India. In this article Oral and written sources are used. The sources are intensively used to validate the concept of primitive tribe’sreligion of Hill Kharia tribe masked bythe domination of Hindu Since in the 20th century. The religious practices and belief are known as primitive tribal religion of the Hill Kharia Tribe believes that Dharma Devota/Thakura or Thakurani (Sun God / Earth God) is the supreme being and humans live in their own life circle known as the religion of the Hill Kharia Tribe believe that morality and ethics as core issues which emanates from the ancestral spirit of respective clans.The sacrifice was a basic ritual practice in the Hill Kharia society of Odisha state in Eastern India. Therefore, this article describes the indigenous wisdom of primitive Hill Kharia Tribe to understand the material and spiritual world.